'The Choice Agenda' in European Health Systems: The Role of 'Middle Class Demands' - Joan Costa-i-Font; Valentina Zigante (London School of Economics and Political Science (LSE), European Institute, 2014)
We examine the role of political economy drivers of the choice agenda in European health systems including middle class electoral support. Building on the reform trajectories and current institutional framework in eight western European countries where there have been significant choice reforms, we explore the preferences for choice and health system satisfaction in those countries. We find provider choice to be supported by middle class demands and health systems satisfaction, but weak evidence of other alternative political motivations for the expansion of provider choice. We conclude that in addition to efficiency improvements, provider choice is largely correlated with the demands for choice among the middle class. The provider choice agenda responds as much to political economy consideration as it does to efficiency arguments.
Keywords: 330; provider choice; health system satisfaction; tax funded health systems; middle class demands